Manganese-Catalyzed Synthesis of Imines from Primary Alcohols and (Hetero)Aromatic Amines - Raydan, Daniel; Friães, Sofia; Viduedo, Nuno; Santos, A. Sofia; Gomes, Clara S. B.; Royo, Beatriz; Marques, M. Manuel B. (Synlett, 2022)
Herein, we describe the synthesis of a wide variety of imines through oxidative coupling of alcohols and aromatic amines catalyzed by Mn complexes bearing N^N triazole ligands. A wide variety of imines in excellent yields (up to 99%) have been prepared. Mn-based catalysts proved to be highly efficient and versatile, allowing for the first time the preparation of several imines containing N-based heterocycles.
Keywords: manganese; catalysis; imines; (hetero)aromatic amines; alcohols